Composition and its impact on shape evolution in dislocated Ge(Si)/Si islands - Liao, X; Zou, J; Cockayne, D; Jiang, Z; Wang, X; Leon, R (2000)
The composition distribution of Ge(Si)/Si (001) islands grown at 700°C by molecular beam epitaxy is investigated using high-spatial resolution x-ray energy dispersive spectrometry in a scanning transmission electron microscope. Island shapes are investigated using cross-section transmission electron microscopy. Results show nonuniformity of the composition distribution in the islands, which affects the evolution of the aspect ratios of height-to-base diameter of dislocated islands. © 2000 American Institute of Physics.